Assessment of the Impacts of Trout Farming on Water Quality Using Macroinvertebrates as Bio-indicators - Rai, Anuradha; Niraula, Archana; Ghimire, Payaswini; Pandey, Aastha; Gurung, Anu; Sharma, Chhatra Mani; Gurung, Smriti (Journal of Institute of Science and Technology, 2018)
The study was conducted to assess the impacts of trout farming on water quality using macroinvertebrates as bio-indicators. Two trout farms were selected for the study, viz., Gandaki Trout Farm (GTF) in Kaski district and Fall & Trout Fish Farm (FTF) in Nuwakot district. Reference and impacted sites were selected in each trout farms from where macroinvertebrates were collected and physico-chemical parameters were measured. Sorensen’s Index and Multiple Site Similarity Index were calculated to compare the macro-invertebrate assemblages between the impact and the reference sites. Water quality classes were also calculated using macroinvertebrate-based tool, NEPBIOS/ASPT scores. Altogether 24 families of macroinvertebrates were observed at GTF and 12 families at FTF. The Sorensen’s Similarity Index was greater than 0.5 between reference and impacted sites at GTF; whereas it was only 0.28 at FTF indicating comparatively low level of similarity. In addition, Multiple Site Similarity Index (0.64) at GTF also indicated high similarity between the macroinvertebrate assemblages. Reference sites showed higher scores with higher diversity of macroinvertebrates. Both farms had suitable water quality for trout (dissolved oxygen and temperature) and most of the physico-chemical parameters did not show significant differences except pH and turbidity at GTF probably due to small scale operation and production. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 175-182